DEVELOPMENT OF MATERIALS PROCESSING USING MAGNETIC FIELD - Hideyuki Yasuda (Jurnal Sains Materi Indonesia, 2007)
DEVELOPMENT OF MATERIALS PROCESSING USING MAGNETIC FIELD. The magnetism, the well-known physical phenomena, has been applied for developing the magnetic materials and devices. To improve the performance of the magnetic materials is obviously important issue in engineering until now. Since the cryogen-free superconducting magnets enable us to impose the relatively high magnetic field such as 10T in the room temperature bore with diameter from 50 mm to 300 mm for weeks, different attempts using the magnetism have been proposed for developing materials processing. The responses of the paramagnetic and the diamagnetic materials to the high magnetic field are often detectable. The high magnetic field has potential to control the micro structure of the ferromagnetic, the paramagnetic and the diamagnetic materials. Therefore, electromagnetic processing of materials (EPM) using the high magnetic field has been realized as a unique technique for controlling the microstructure. The high magnetic field was used to achieve the crystallographically aligned structure, to produce the regular structure in which one phase is regularly aligned in the matrix, to develop the containerless processes by the magnetic levitation and so on. In this paper, the principle of EPM is briefly explained. Then, some applications of the high magnetic field to the materials processing are presented; (1) the crystallographically aligned structure of the Bi-Mn system and (2) the regular structure formation in the Al-In monotectic alloys.